Left Atrial Size; a Missing Component in Scoring Systems for Predicting Atrial Fibrillation Following Coronary Artery Bypass Surgery - Karimi, Abbasali (Acta Cardiol Sin, 2020)
BACKGROUND: Several risk factors have been associated with the development of postoperative atrial fibrillation (AF). However, some important factors that may play substantial roles have been neglected in the final suggested risk models. In this study, we aimed to derive a new clinical risk index to predict AF in coronary artery bypass graft (CABG) patients. METHODS: In this retrospective cohort study we enrolled 3047 isolated CABG patients. A random sample of 2032 patients was used to derive a risk index for the prediction of post-CABG AF. A multivariate logistic regression model identified the independent preoperative predictors of post-CABG AF, and a simple risk index to predict AF was constructed. This risk index was cross-validated in a validation set of 1015 patients with isolated CABG. RESULTS: Post-CABG AF occurred in 15.9% and 15.7% of the patients in the prediction and validation sets, respectively. Using multivariate stepwise analysis, four preoperative variables including advanced age, left atrial (LA) enlargement, hypertension and cerebrovascular accident contributed to the prediction model (area under the receiver operating characteristic curve curve = 0.66). The effect of advanced age appeared to be dominant [age ≥ 75 years; odds ratio: 4.134, 95% confidence interval (CI): 2.791-6.121, p < 0.001]. Moderate to severe LA enlargement had an odds ratio of 2.176 (95% CI: 1.240-3.820, p = 0.013) for developing AF in our risk index. CONCLUSIONS: LA size was an important factor in risk stratification of post-CABG AF, which remained significant in the final model. Future scoring system studies might benefit from the use of this variable to obtain a more robust predictive value.